Building an Academic Law Library from Scratch. (December 2021) - Bennett, Greg
Abstract: Goldsmiths, University of London, started teaching LLBs in Law in 2019/2020. Greg Bennett was hired in 2018 to be the subject librarian for law, and to stock the library before teaching commenced. In this article, based on his presentation at the BIALL Online Annual Conference in June 2021, the author will discuss his decision-making and selection processes regarding his choices about what to include, and what not to include in the collection.